2019
DOI: 10.1038/s41559-019-0909-z
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoproteomics resolves sloth relationships

Abstract: The living tree sloths Choloepus and Bradypus are the only remaining members of Folivora, a major xenarthran radiation that occupied a wide range of habitats in many parts of the western hemisphere during the Cenozoic, including both continents and the West Indies. Ancient DNA evidence has played only a minor role in folivoran systematics, as most sloths lived in places not conducive to genomic preservation. Here we utilise collagen sequence information, both separately and in combination with published mtDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 64 publications
(81 reference statements)
7
85
1
1
Order By: Relevance
“…Therefore, the newly described metacarpal is either further evidence, or new evidence, that Xenarthra was indeed present on Antarctica during the Eocene depending upon one's stance with regard to prior controversies. This record is consistent with the estimated timing of origin for Folivora by the early Eocene, and of Xenarthra in the Paleocene (e.g., Presslee et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the newly described metacarpal is either further evidence, or new evidence, that Xenarthra was indeed present on Antarctica during the Eocene depending upon one's stance with regard to prior controversies. This record is consistent with the estimated timing of origin for Folivora by the early Eocene, and of Xenarthra in the Paleocene (e.g., Presslee et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Xenarthra is proposed to have originated in South America, and thus is plausibly anticipated in the Paleogene of Antarctica given inferred land connections between these continents during the early Cenozoic (Woodburne & Case, 1996;Delsuc et al, 2019;Presslee et al, 2019). The new metacarpal extends the known Paleogene geographic range of Xenarthra into Antarctica.…”
Section: Discussionmentioning
confidence: 88%
“…Lett. 16: 20190947 molecular evidence is consistent with the synchronous arrival of terrestrial organisms to the region approximately 33.9 ± 1 Ma, while others clearly arrived through multiple overwater dispersal events throughout the Neogene or even earlier [8,13,15,35,36,[44][45][46][47][48][49][50]. Furthermore, molecular phylogenetic studies have suggested a similar Oligocene arrival for at least some anuran taxa on the Puerto Rican and Hispaniolan banks, such as Leptodactylus [13] and Peltophryne [15].…”
Section: (C) Descriptionmentioning
confidence: 62%
“…However, these results are preliminary inasmuch as the proposed position of Borikenomys is likely to evolve with additional morphological data. If this phylogenetic link is confirmed, these endemic giant Caribbean rodents could have a remarkable antiquity on the islands (as for Caribbean sloths [27,28] and coquí frogs [75]) and thus could represent a unique case of long-lived insular rodent lineage. Alternatively, these Oligocene Puerto Rican chinchilloids could have become extinct without descendants.…”
Section: Discussionmentioning
confidence: 99%